Konsep dan Pembaruan Residivisme dalam Hukum Pidana di Indonesia (Concept and Reform of Recidivism in Criminal Law in Indonesia) - Prianter Jaya Hairi (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2018)
The legal arrangement of additional penalty for repetition of crime (recidivism) as stipulated in Indonesian Criminal Code has been considered quite complicated to be executed. The draft of the New Indonesian Penal Code Bill brings changes to the concept of recidivism. This study intends to examine the concept of recidivism in the doctrine, in its current arrangement, in the draft of the New Indonesian Penal Code Bill, and to examine the implications of the concepts’ changing for criminal law enforcement in general. In the discussion it is known that the existing Criminal Code, applied the concept of special recidivism with the intermediate system, that will be transformed into a system of "Algemene Recidive" or a general recidive, which means that it would no longer differentiates the type of crime or group of repeated offenses. The draft of the New Indonesian Penal Code Bill stipulates that the period of time a person is charged due to a recidive is an additional "5 (five) years" after undergoing all or part of the principal punishment imposed or after the principal criminal sentence has been abolished, or when the crime was committed, the previous sentences has not been expired (still serving a criminal sentence). Some of the implications of these changes are to include a relatively simpler concept of recidivism in the draft Criminal Code compare to what is currently regulated in the Criminal Code. Therefore, this concept will make it easier for law enforcers to implement recidivism. Implementation of the concept of recidivism should be followed by changes in criminal procedural instruments (RUU KUHAP) and other regulations related to technical procedures in each law enforcement agency. Changes in the recidivist system also need to be followed by efforts to reform the penitentiary system, so that the level of recidivism would not increased.AbstrakPengaturan hukum mengenai pemberatan hukuman karena pengulangan tindak pidana (residivisme) yang terdapat dalam Kitab Undang-undang Hukum Pidana (KUHP) selama ini dipandang cukup rumit untuk diterapkan. RUU Hukum Pidana membawa perubahan terhadap konsep residivisme. Artikel ini bermaksud untuk mengkaji bagaimana konsep residivisme dalam doktrin, dalam pengaturannya saat ini, dalam draft RUU Hukum Pidana, serta mengkaji implikasi perubahan konsep tersebut bagi penegakan hukum pidana secara umum. Dalam pembahasan diketahui bahwa KUHP yang selama ini berlaku, menerapkan sistem residivis khusus dengan sistem antara, akan diubah menjadi sistem “Algemene Recidive” atau recidive umum, yang artinya sudah tidak lagi membedakan jenis tindak pidana atau kelompok jenis tindak pidana yang diulangi. RUU Hukum Pidana diantaranya mengatur bahwa jangka waktu seseorang dikenakan pemberatan akibat recidive ialah “5 (lima) tahun” setelah menjalani seluruh atau sebagian pidana pokok yang dijatuhkan atau pidana pokok yang dijatuhkan telah dihapuskan, atau pada waktu melakukan Tindak Pidana, kewajiban menjalani pidana pokok yang dijatuhkan terdahulu belum kedaluwarsa (masih menjalani pidana). Beberapa implikasi dari perubahan tersebut antara lain bahwa konsep recidivis dalam draf RUU Hukum Pidana relatif lebih simpel dibandingkan dengan yang diatur dalam KUHP yang berlaku saat ini. Oleh sebab itu konsep tersebut akan lebih memudahkan penegak hukum dalam penerapannya. Penerapan konsep residivis perlu diikuti dengan perubahan instrumen hukum acara pidana (RUU KUHAP) serta peraturan lain terkait prosedur teknis di masing-masing lembaga penegak hukum. Perubahan sistem residivis juga perlu diikuti dengan upaya pembenahan terhadap sistem pembinaan lembaga pemasyarakatan, agar tingkat residivisme tidak semakin tinggi.